AWARENESS CAMPAIGNS AND HAND HYGIENE PRACTICE AMONG SECONDARY SCHOOL STUDENTS - Olatunji, Rotimi Williams; Taiwo, Noeem Thanny (Journal of Environmental Science and Sustainable Development, 2023)
Nigeria's low level of sanitation hygiene provoked the increasing prevalence and containment of infectious diseases such as bird flu, acute respiratory infections, Ebola, Lassa fever, polio, diarrheal, pneumonia, and dysentery. These diseases can attack vulnerable groups like children. Therefore, awareness of hand hygiene practices is still needed to prevent the spread of diseases. This study analyzed the exposure to campaign messages on hand washing and hand hygiene sanitation among secondary school students in Lagos State, Nigeria. A total of 620 students participated in the study and were selected through multi-stage sampling methods. Research instruments adopted included questionnaires and observation of hand hygiene facilities and practices among students. Quantitative data were analyzed through the Statistical Package for Social Sciences (SPSS). Findings show that about 97% of respondents are aware of the need to wash their hands. Furthermore, interpersonal sources of information on hand hygiene available to respondents included parents and family members (58.9%), followed by medical officers (13.4%), public health campaign organizations (11.7%), and teachers (9.9%). The three most dominant influences on hand washing practice among respondents are parents (46.4%), teachers (23.3%), the media (14.5%), and private business organizations (12.1%) in that order. Based on the correlation coefficient (r = 0.256; p = 0.000), the study established a significant positive relationship between exposure to campaign messages and hand sanitation among the study group, indicating that exposure to hand sanitation messages positively influences good handwashing behavior among school children. This study has implications for government authorities, policymakers, and development partners on the need to engage traditional and new media channels to complement interpersonal sources of information to enhance proper hand sanitation among students in Nigeria and other sub-Saharan African countries.